Reception of Digital Novel Readers (Role of Indonesian Readers in Wattpad Application) - Yanti, Prima Gusti; Ibrahim, Nini; Zabadi, Fairul; Rahman, Fauzi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
In digital novels, readers get a room for comment, give a suggestion, or just give hope herself regarding the novel, for instance about characters, settings, and plot creation. The aim of this study is for finding the perception reader to digital novels. This method used of this Study is qualitative descriptive. The Research data sources are from the novels of Wattpad app with the most reader status from 3 selected novels randomly i.e Dosen Bucin, Still, I Do, and Mantan Kakak Ipar Rasa Pacar. the study used pragmatics approach. Pragmatics Approach is used because in the study this aim is for investigating the response of readers through aesthetics reception Jauss on literary texts in Novels on Wattpad. Techniques used to collect data in the study is a watch notes and a study bibliography. Research results show that the most dominant reception lies in thesis 2. This domination reaches the percentage of 71.5% which means that is at a high level. Thesis 2 in Jauss literary reception have meaning that a literary work can awaken the memory of the reader so that it creates a special emotional attitude. In this context, the reader has a horizon of expectations at the beginning, middle, and end stages of the content of the literary work. The process of receiving the text (reading process) is the reader's subjective impression (awakening the reader’s memory and appearing attitude emotional).